(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Suppose that E is a normed space. In this work, using Brzde k fixed point theorem, we prove the Hyers-Ulam stability of the Pexiderized additive-quadratic functional equation align* f(x+y)+f(x-y)+h(x+y)=2f(x)+2f(y)+h(x)+h(y) align* for all x,yE.